Vestibular, saccadic and fixation abnormalities in genetically confirmed Friedreich ataxia - Fahey, Michael C.; Cremer, Phillip D.; Aw, Swee T.; Millist, Lynette; Todd, Michael J.; White, Owen B.; Halmagyi, Michael; Corben, Louise A.; Collins, Veronica; Churchyard, Andrew J.; Tan, Kim; Kowal, Lionel; et al. (Brain (London, England : 1878), 2008)
Friedreich ataxia (FRDA), the commonest of the inherited ataxias, is a multisystem neurodegenerative condition that affects ocular motor function. We assessed eye movement abnormalities in 20 individuals with genetically confirmed FRDA and compared these results to clinical measures. All subjects were assessed with infrared oculography. Fifteen individuals underwent a full protocol of eye movement recordings. Ten subjects were analysed using two-dimensional scleral coil equipment and five using three-dimensional scleral coil recording equipment. We also recorded visual quality of life, Sloan low contrast letter acuity and Friedreich Ataxia Rating Scale scores to compare to the visual measures. Whilst saccadic velocity was essentially normal, saccadic latency was prolonged. The latency correlated with clinical measures of disease severity, including the scores for the Friedreich Ataxia Rating Scale and the Sloan low contrast letter acuity tests. Fixation abnormalities consisting of square wave jerks and ocular flutter were common, and included rare examples of vertical square wave jerks. Vestibular abnormalities were also evident in the group, with markedly reduced vestibulo-ocular reflex gain and prolonged latency. The range of eye movement abnormalities suggest that neurological dysfunction in FRDA includes brainstem, cortical and vestibular pathways. Severe vestibulopathy with essentially normal saccadic velocity are hallmarks of FRDA and differentiate it from a number of the dominant spinocerebellar ataxias. The correlation of saccadic latency with FARS score raises the possibility of its use as a biomarker for FRDA clinical trials.